More 1-2-3 magic [videorecording (DVD)] : encouraging good behavior, independence and self-esteem - Booth, Edward C.; Phelan, Thomas W., 1943-; Turlow, Pam (ParentMagic, Inc., 2004)
Dr. Phelan explains how to get your children to do the good things you want them to do, such as getting up and out in the morning, eating, going to bed and picking up after themselves. The program teaches strategies for encouraging your children's independence and healthy self-esteem.